2008
DOI: 10.1021/nl8021626
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic and ab Initio Study of the Formation of Graphite and Carbon Nanotubes from Thermal Decomposition of Silicon Carbide

Abstract: We report an experimental and first-principles study of the thermal decomposition of 6H-SiC wafers, yielding graphite on the Si-terminated face and carbon nanotubes on the C-terminated face. The asymmetry of the carbon structure formation mechanisms is rationalized in terms of the different termination geometries of the opposite SiC faces. First-principles modeling reveals that horizontal, xr-delocalized carbon structures form on the Si-terminated face. The bonding network geometry of the C-terminated face fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[14,15] In addition, annealing single-crystal SiC under ultrahigh vacuum can also lead to growth of ultrathin graphite or few-layer graphene on the Si-terminated surface with the layer thickness determined predominantly by temperature. [16][17][18][19] However, these promising epitaxial growth methods have only been employed for the purpose of fundamental studies so far. The resulting graphene sits on a single-crystal surface and the yield of graphene is rather low.…”
mentioning
confidence: 99%
“…[14,15] In addition, annealing single-crystal SiC under ultrahigh vacuum can also lead to growth of ultrathin graphite or few-layer graphene on the Si-terminated surface with the layer thickness determined predominantly by temperature. [16][17][18][19] However, these promising epitaxial growth methods have only been employed for the purpose of fundamental studies so far. The resulting graphene sits on a single-crystal surface and the yield of graphene is rather low.…”
mentioning
confidence: 99%
“…It should be noted that in the difference spectra, a sharp π* resonance peak with a negligibly weak σ* resonance feature is observed at θ = 30°, while the former disappeared at θ = 90°. To date, many NEXAFS spectra have been reported for graphene ,, and molecules with conjugated bonds on metal or semiconductor surfaces. In those systems, one π-orbital overlaps with another across the intervening σ-bond.…”
Section: Resultsmentioning
confidence: 99%
“…So far, only a few theoretical studies have been reported regarding the initial stage of CNT formation on the SiC C-face. On the basis of ab initio calculations and photoemission results, Levita et al proposed that open-ended CNTs initially grow vertically as a C-sp 2 network structure, followed by closure of the CNT tips after the tube walls have reached sufficient length . Irle and Kusunoki’s group performed density-functional tight-binding molecular dynamics (DFTB/MD) simulations for graphene and CNT formation on the SiC surface by thermal decomposition. In contrast to the former model, they demonstrated that a large carbon network is formed at the terrace site on the SiC C-face at 1500 K by both removing Si atoms and subsequent carbon rearrangement, resulting in carbon nanocap formation at the initial stage.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 284.6 eV, observed on all survey spectra, is generated by photoelectrons emitted from the C 1s core level. 29 The XPS of plasma treated samples reveals the presence of carbon and fluorine atoms at the CNT-surface. For increasing functionalization time (Table S1), the amount of fluorine species grafted at the CNT surface increases, while the amount of oxygen and nitrogen slightly decreases.…”
Section: Resultsmentioning
confidence: 99%